2014
DOI: 10.1159/000365972
|View full text |Cite
|
Sign up to set email alerts
|

Defective Inflammatory Monocyte Development in IRF8-Deficient Mice Abrogates Migration to the West Nile Virus-Infected Brain

Abstract: IRF8 (interferon-regulatory factor-8) plays a critical role in regulating myeloid cell differentiation. However, the role of this transcription factor in the development of Ly6C+ inflammatory monocytes and their migration to the infected brain has not been examined. We have previously shown that West Nile virus (WNV) infection of wild-type (WT) mice triggers a significant increase in numbers of Ly6C+ monocytes in the bone marrow. These cells traffic via the blood to the infected brain, where they give rise to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…3A). Previous studies have shown that migration of bone marrow (BM) monocytes to inflamed tissue sites is dependent on CCL2/CCR2 signaling 2629 . We observed that CCL2 was produced at significantly lower levels in Day 8 CVB3-infected Muc-1 KO pancreata than in WT pancreata (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A). Previous studies have shown that migration of bone marrow (BM) monocytes to inflamed tissue sites is dependent on CCL2/CCR2 signaling 2629 . We observed that CCL2 was produced at significantly lower levels in Day 8 CVB3-infected Muc-1 KO pancreata than in WT pancreata (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mice lacking IRF8 have reduced numbers of monocytes and dendritic cells (DCs), have elevated neutrophil counts, exhibit defective antimicrobial immunity, and develop chronic myelogenous leukemia (CML)-like disease. [1][2][3][4][5][6][7][8][9] In humans, IRF8 mutations are associated with immunodeficiency, and decreased IRF8 expression has been observed in both acute myelogenous leukemia (AML) and CML patients. [10][11][12] Previous studies have shown that IRF8 promotes monocyte and DC production but limits neutrophil production.…”
Section: Introductionmentioning
confidence: 99%
“…The enriched down-regulated genes found in this study (Harcourt et al 2003a, b), IL2 (Noma et al 1996), IL3 (Bertrand et al 2015), IL4 (Puthothu et al 2006), IL9 (Dodd et al 2009) and STAT6 (Srinivasa et al 2016) were responsible for progression of respiratory syncytial virus infection, but these genes may be linked with progression of SARS-CoV-2 infection. Many previous studies have confirmed the roles of enriched down-regulated genes such as IL12B (Mueller et al 2004) (Liu et al 2009), ETS1 (Posada et al 2000), STAT5A (Warby et al 2003), THY1 (Lu et al 2011), IL16 (Caufour et al 2001), HLA-B (Martin et al 2007), HLA-C (Apps et al 2013), HLA-DPA1 (Wasityastuti et al 2016), HLA-DPB1 (Lambert et al 2015), HLA-DQA1 (Tibbs et al 1996), HLA-DRB1 (Chi et al 2013), PSMB10 (Deng et al 2019), BCL2 (Zuckerman et al 2001), TOLLIP (toll interacting protein) (Li et al 2016a, b), VCAM1 (Koraka et al 2004), RAG1 (Winkler et al 2017), IRF8 (Terry et al 2015), EBI3 (Gehlert et al 2004), EGR1 (Baer et al 2016), IL27 (Swaminathan et al 2013) and BID (BH3 interacting domain death agonist) (Hsu et al 2003) were linked with development of various viral infections, but these genes may be associated with advancement of SARS-CoV-2 infection. Previous investigation demonstrated that enriched downregulated genes such as IL17A (Wang et al 2016) (Du et al 2014), RAG2 (Wu et al 2010), CASP3 (Takahashi et al 2013), S1PR1 (Zha...…”
Section: Discussionmentioning
confidence: 77%